Regulating Greenhouse Gases in Canada: Constitutional and Policy Dimensions - Hsu, Shi-Ling; Elliot, Robin (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractCanada’s greenhouse gas emissions have risen dramatically since the 1997 negotiation of the Kyoto Protocol, and that rise has continued through Canada’s 2002 ratification of the Protocol. Along with economic dislocation, constitutional barriers to regulation have sometimes been cited as the reason for caution in regulating greenhouse gases. This article critically evaluates the constitutional arguments and examines the policy considerations surrounding various regulatory instruments that might be used to reduce greenhouse gases. We conclude that the Canadian constitution does not present any significant barriers to federal or provincial regulation and that policy considerations strongly favour the use of two instruments: a federal carbon tax to impose a marginal cost on emissions and the Canadian Environmental Assessment Act to review federal projects that may increase greenhouse gases.